Enhancing sensitivity of surface plasmon resonance biosensors by functionalized gold nanoparticles: size matters - Špringer, Tomáš; Ermini, Maria Laura; Špačková, Barbora; Jabloňků, Jani; Homola, Jiří (Analytical chemistry, 2014)
We study how the size of spherical gold nanoparticles (AuNPs) influences their ability to enhance the response of optical biosensors based on surface plasmon resonance (SPR). We present a theoretical model that relates the enhancement generated by the AuNPs to their composition, size, and concentration, thus allowing for accurate predictions regarding the SPR sensor response to various AuNPs. The effect of the AuNP size is also investigated experimentally using an SPR biosensor for the detection of carcinoembryonic antigen (CEA) in which AuNPs covered with neutravidin (N-AuNPs) are used in the last step of a sandwich assay to enhance the sensor response to biotinylated secondary antibody against CEA. The experimental data are in excellent agreement with the results of the theoretical analysis. We demonstrate that the sensor response enhancement generated by the N-AuNPs is determined by (i) the sensor sensitivity to N-AuNP surface density (Sσ) and (ii) the ability of the N-AuNPs to bind to the functionalized surface of the sensor. Our results indicate that, while Sσ increases with the size of the N-AuNP, the ability of the functionalized surface of the sensor to bind the N-AuNPs is affected by steric effects and decreases with the size of N-AuNP.
Keywords: biosenzitivní techniky; zlato; Surface Plasmon Resonance; Limit of Detection; kovové nanočástice; Gold; velikost částic; limita detekce; povrchová plasmonová rezonance; Metal Nanoparticles; Particle Size; Biosensing Techniques